Transitionen im Jugend- und jungen Erwachsenenalter Ergebnisse der Schweizer Längsschnittstudie TREE - scharenberg, Katja; Hupka-Brunner, Sandra; Meyer, Thomas; Bergman, Manfred Max (Seismo, 2018)
Much like the first volume published in 2011, the second volume of this anthology series gathers a selection of analyses which are empirically based on the data of the Swiss panel study TREE (Transitions from Education to Employment). The contributions of this volume carry on the investigation of the critical transitions during youth and young adulthood, drawing on sociological, economic, psychological and pedagogical research questions and thus highlighting the analytic and pluri-disciplinary research potential of the TREE data. One of the topical foci is the longterm influence of social origin on education and labour market pathways, particularly with regard to access to higher education.